KUALITAS PELAYANAN PADA KANTOR PERPUSTAKAAN DAN ARSIP KABUPATEN KAMPAR - Rafidah Zainah Zainah; Jaspar Jas Jas; Daeng Ayub Natuna Ayub Natuna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Formulation of the problem in this research is how high service quality in libraries and archives office of Kampar regency. This research purposes is to know service quality levels in libraries and archives office of Kampar regency. Benefits of research is this research can be used as inputs and consideration of the importance of service quality. This is a descriptive researchs with a quantitative approach. Population in this research were 60 peoples. Sampling in this research using proportionate stratified random sampling technique. Instrumens used questionnaire with 50 items of questions. Service quality in libraries and archives office of Kampar regency measured with indicator reliability, responsivenees, assurance, empathy and tangible. Of the survey results revealed that service quality in libraries and archives office of Kampar regency included in the high category. Keyword: Service Quality, Libraries and Archives Office